Sabina de la Cruz, Javier Huerta, Emilio Miró, Jaime Olmedo, José Paulino, Fanny Rubio: Rafael Morales. Homenaje. - Martín Martínez, Rafael (Dicenda. Estudios de lengua y literatura españolas, 1996)
Sin resumen